Lung injury after asphyxia and hemorrhagic shock in newborn piglets: Analysis of structural and inflammatory changes - Weber, Birte; Mendler, Marc Robin; Lackner, Ina; Von Zelewski, Alexander; Hoefler, Severin; Baur, Meike; Braun, Christian Karl; Hummler, Helmut; Schwarz, Stephan; Pressmar, Jochen; Kalbitz, Miriam (PLoS ONE, 2019)
Objective Asphyxia of newborns is a severe and frequent challenge of the peri- and postnatal period. The purpose of this study was to study early morphological, immunological and structural alterations in lung tissue after asphyxia and hemorrhage (AH). Methods 44 neonatal piglets (age 32 hrs) underwent asphyxia and hemorrhage (AH) and were treated according to the international liaison committee of resuscitation (ILCOR) guidelines. For this study, 15 piglets (blood transfusion (RBC) n = 9; NaCl n = 6, mean age 31 hrs) were randomly picked. 4 hours after ROSC (return of spontaneous circulation), lung tissue and blood samples were collected. Results An elevation of myeloperoxidase (MPO) activity was observed 4 hrs after AH accompanied by an increase of surfactant D after RBC treatment. After AH tight junction proteins Claudin 18 and junctional adhesion molecule 1 (JAM1) were down-regulated, whereas Occludin was increased. Furthermore, after AH and RBC treatment dephosphorylated active form of Connexin 43 was increased. Conclusions AH in neonatal pigs is associated with early lung injury, inflammation and alterations of tight junctions (Claudin, Occludin, JAM-1) and gap junctions (Connexin 43) in lung tissue, which contributes to the development of lung edema and impaired function.
CRIS-Team Scopus Importer:2020-12-21